Comparação entre valores de ensaios experimentais e calculados da resistência ao embutimento da madeira de Pinus taeda L. - Almeida, Diego Henrique de; Ferro, Fabiane Salles; Varanda, Luciano Donizeti; Christoforo, André Luis; Lahr, Francisco Antonio Rocco; Molina, Julio Cesar [UNESP]; Calil Junior, Carlito (FapUNIFESP (SciELO), 2014)
To design connections between timber parts with metal dowels (nails or bolts), two phenomena must be considered: bending of the metal dowel and the embedment strength in the wood. The Brazilian Standard ABNT NBR 7190:1997 proposes the methods used in the laboratory tests to determine the embedment strength with the metal dowell and, in the absence of testing, specifies relations to calculate the embedment strength from the compression strength. The aim of this research was to compare the embedment strength values obtained by experimental tests and calculated by the relationships established by the Brazilian Standard ABNT NBR 7190:1997. By the results of the hypothesis tests, it was possible to conclude that the estimate of the embedment strength parallel to the grain proposed by the Brazilian standard ABNT NBR 7190:1997, establishing equivalence with the strength compression results in the same direction, must be effective to the wood species Pinus taeda L., however, the same was not found in the perpendicular direction with respect to the grain, possibly explained by the αe values in the equation to calculed fe90.
Comparison between experimental tests and calculed values for the embedment strength of Pinus taeda L. Wood
Keywords: Connections; Embedment strength; Timber structures